International Trade Dynamics, Resiliency, and Economic Growth of the Philippines - Liane Vina G. Ocampo; Rosario B. Gumban; Jessie Anne T. Demetillo (Business, Management and Economics: Research Progress Vol. 9, 2024)
This study examines the intricate relationship between Gross Domestic Product, exports, and imports in the Philippines, using the Vector Error Correction Model to capture both the short and long-run dynamics of these economic variables. By utilizing annual data from 1984 to 2023, the study identifies a significant long-term equilibrium among GDP, exports, and imports. Even though export growth positively influences GDP in the long run, an overreliance on imports detracts from the economic output by fostering a trade balance, indicating the need for increased domestic production. The short-run findings reveal a rapid adjustment of GDP toward long-term balance, suggesting resilience in the face of external shocks such as the COVID-19 pandemic. However, exports demonstrate slower adjustments due to global demand fluctuation and supply chain disruption. Granger causality tests also show that greater GDP and export activities have led to greater imports but do not directly impact GDP growth. Variance decomposition analysis emphasizes exports’ growing role in GDP variance over time. A focus on diversification in terms of export products and improving the business environment is highlighted in the result as the country transitions from an agricultural to an industrialized economy. The concern of the study over policy formulation for trade imbalances and the promotion of economic growth underlines the overall emphasis. This research enhances the understanding of macroeconomic variables that influence trade and provides important insights for policymakers and other future researchers who seek to navigate the complexities of international trade and economic development in the context of developing economies.